The Availability of Online-Based East Kalimantan Folktales: A Call for Preservation - Anna Anganita Theresia Latumeten (Faculty of Letters Universitas Balikpapan, 2022)
Up until today, most people living in East Kalimantan still have a little knowledge and understanding about their folktales. This might be caused by the limited availability of the stories everywhere, including on the internet. This paper aims to report on the availability of online-based East Kalimantan folktales by searching on the web, utilizing the most commonly used search engines in Indonesia. The search found that only 17 folktales are available worldwide, and most of these texts and non-texts materials have yet to exist in decent or official forms. This calls for a quick action of preservation in order not to let these cultural assets to extinct in the middle of the threat from the vast growing internet and mainstream entertainment.